New and Simple Approach for Preventing Postoperative Peritoneal Adhesions: Do not Touch the Peritoneum without Viscous Liquid—A Multivariate Analysis - Erhan Aysan; Hasan Bektas; Feyzullah Ersoz; Serkan Sari; Arslan Kaygusuz; Gulben Erdem Huq (Obstetrics and Gynecology International)
Background. Postoperative peritoneal adhesions (PPAs) are an unsolved and serious problem in abdominal surgery. Method. Viscous liquids of soybean oil, octyl methoxycinnamate, flax oil, aloe vera gel, and glycerol were used in five experiments, using the same methodology for each. Liquids were applied in the peritoneal cavity before and after mechanical peritoneal trauma. Results were evaluated by multivariate analysis. Results. Compared with the control group, macroscopic and microscopic adhesion values before (P<.001) and after (P<.05) application of viscous liquids significantly reduced PPAs. Values were significantly lower when liquids were applied before rather than after peritoneal trauma (P<.0001). Discussion. Viscous liquids injected into the peritoneal cavity before or after mechanical peritoneal trauma decrease PPA. Injection before trauma was more effective than after trauma. In surgical practice, PPA formation may be prevented or decreased by covering the peritoneal cavity with an appropriate viscous liquid before abdominal surgery.